Factors Influencing the Performance of Posyandu Cadres in Sukamanis Village Kadudampit Health Center Sukabumi District - Sodikin, Elisya Handayani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The purpose of this study was to determine the factors that influence the performance of posyandu cadres in Sukamanis Village, Kadudampit Health Center Working Area, Sukabumi Regency. Methods: Type of correlational research with a cross sectional approach. The population was posyandu cadres with a sample of 53 people using total sampling technique. Data collection techniques using questionnaires. The instrument has validity p-value <0.05 and reliability r> 0.7. Statistical analysis using logistic regression. Results: The results showed that motivation (p=0.004), education (p=0.004), knowledge (p=0.018), and the role of health workers (p=0.046) affect the performance of posyandu cadres. Conclusion: Motivation, education, knowledge, and the role of health workers have an influence on the performance of posyandu cadres. It is expected that health workers play an active role in encouraging the improvement of the performance of posyandu cadres.